Training Based on the Participantsâ Activeness to Improve Teachersâ Understanding toward Authentic Assessment in Elementary School - Maryani, Ika; Martaningsiha, Sri Tutur; Fatmawati, Laila (Sebelas Maret University, 2016)
Problems that occur in the implementation of 2013 Curriculum is the lack of understanding in the learning process assessment and learning outcomes. The concept of thorough learning takes longer time, it also requires teachers understanding to the ability of the student individually. Teachers also do not fully understand the concept of authentic and continuous assessment. The aim of this study is to improve the classroom teachersâ understanding toward authentic assessment with training model based on participantsâ activeness. This research used Classroom Action Research approach with two cycles. The techniques of collecting data are questionnaires (self-assessment), interviews, and portfolios. The data were analyzed using triangulation with consideration to the three types of data. The result showed an improvement in the teachers understanding on authentic assessment. This is indicated by the improvement of the average from pretest to posttest in the cycle 1 is 9.25 and cycle 1 to cycle 2 is 13.19.